Pharmacokinetics and effect of intravenous nalbuphine in weaned Holstein calves after surgical castration. Issue 2 (12th August 2013) - Coetzee, J. F.; Lechtenberg, K. F.; Stock, M. L.; KuKanich, B.
<x xml:space="preserve">Abstract</x> The objective of this study was to investigate the pharmacokinetics and effect of nalbuphine administered intravenously to calves immediately prior to surgical castration. Ten healthy calves were randomly assigned to two treatments (n = 5): (i) 0.9% sodium chloride (CONT) placebo, (ii) nalbuphine hydrochloride (NAL) (0.4 mg/kg). Blood samples collected over 10 h postcastration were analyzed for nalbuphine and cortisol concentrations. Additionally, heart rate, respiratory rate, rectal temperature, and step count was compared between groups using a random‐effects mixed model. Changes in behavior and attitude were assessed using a six‐point ordinal scoring system and compared using chi‐square analysis. Plasma NAL concentrations were only detectable for 3 h postadministration (T½ = 0.68 h; Range: 0.53–0.79 h). There was no effect of NAL treatment prior to castration on cortisol concentrations (P = 0.99), heart rate (P = 0.73), respiratory rate (P = 0.59), rectal temperature (P = 0.22), and step count (P = 0.08) but fewer calves showed signs of head shaking, kicking, and tail flicking in the NAL group compared with the CONT group (P = 0.036). Therefore, we conclude that a single intravenous injection of nalbuphine at 0.4 mg/kg reduced some pain‐related behaviors but did not significantly eliminate the physiological signs of distress in calves after surgical castration.